Algeria : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Algeria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights the important challenges Algeria continues to face as a result of the fall in oil prices four years ago. Despite sizable fiscal consolidation in 2017, the fiscal and current account deficits remain large. Real GDP growth slowed sharply, driven mainly by a contraction in hydrocarbon production, although growth in the nonhydrocarbon sector was stable. Unemployment increased to 11.7 percent in September 2017 from 10.5 in September 2016 and remains particularly high among youth and women. Average inflation declined from 6.4 percent in 2016 to 5.6 percent owing to slowing inflation for manufactured goods and services, and stood at 3.4 percent year over year in April 2018.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet